Techno-economic reservoir simulation model for CO2 sequestration evaluation - Khan, Charwarwan Muhssen Hussen (Curtin University, 2013)
This thesis focuses on the recovery factor of natural gas production and storage by injecting CO2 into a natural gas reservoir. This task is performed by applying reservoir simulation software (Roxar-Tempest) to experimental data produced by Clean Gas Technology Australia for a North West Shelf Australian field. In addition, the economic feasibility of the process is evaluated in terms of development costs, CO2 capture and storage costs, carbon credits and carbon tax.